ANALISIS PERBEBAAN PENDAPATAN USAHATANI PADI SAWAH SEBELUM DAN SETELAH MENERIMA BANTUAN PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) (STUDI KASUS PADA GAPOKTAN PANCA USAHA DIDESA WAKANGKA KECAMATAN KAPONTORI KABUPATEN BUTON - Muzuna, Muzuna (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2017)
Abstract The problem formulation of this research are: (I) How big is the level of farming income of wetland rice before and after receiving financial assistance from the PUAP program at the Panca Usaha GAPOKTAN in Wakangka Village, Kapontori Sub-district, Buton Regency; and (2) How much is the level of effectiveness of the PUAP program funding assistance to the level of wetland rice farming income in Wakangka Village, Kapontori Sub-district. The purpose of this study were (1) to find out the level of wetland rice farming income level before and after receiving financial assistance from the PUAP program at the Panca Usaha GAPOKTAN in Wakangka Village, Kapontori Sub-district; and (2) To determine the level of effectiveness of PUAP funding assistance to the level of wetland rice farming income in Wakangka Village, Kapontori Sub-district. This research was carried out in the village of Wakangka, Kapontori Sub-district, Buton Regency, from August to September 2016 by taking 30 farmers as samples. The analysis used in this study farming acceptance is the multiplication between production and selling price, farming costs are all expenditures used in a farm, and net income is the difference between income and expenditure. The return can be written as follows: TRi = Yi x Pyi; Total cost (TC) = FC + VC and farm income is the difference between revenue and all costs. (Pd) = TR - TC. After the income is known, quantitative analysis is then analyzed, then paired sample t-test is carried out with the help of SPSS 20 for windows. Based on the results of the study and discussion shows that there is a difference in the average income level of the farmer's group (GAPOKTAN) Panca Usaha in Wakangka Village before and after receiving PUAP funding, which is IDR. 839,666.67 or an increase of 7.77%. The average income of farmers before receiving PUAP assistance amounted IDR IDR10,805,090.00 after receiving PUAP assistance amounting to IDR 11,644,756.67 with an average land area of 0.94 Ha. PUAP program in Panca Usaha GAPOKTAN Wakangka Village is said to be effectively seen from the outcome variables which consist of the level of income and revolving PUAP funds before and after receiving PUAP program assistance. The results of the t-test showed a significant increase in income (sig value under 0.05).   Keywords: Different income, PUAP, lowland rice farming, Gapoktan